MEMBANGUN KARAKTER PROFETIK - Reky Lidyawati (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2017)
The problematic character in the life of society continues to experience increasingly complex developments, the advancement of science and technology has reformed the character probletics not only in the real world but also in cyberspace. This morality problematic must be overcome to realize the society that berakhlaqulkarimah. Strategies that can be done in tackling this problematic is to build a prophetic character. Character is related to character, character, psychological traits, character, personality or morals, then if we depart from human nature as a creature that can be educated, in fact the character can be directed and formed to be better than the previous. If there is someone who thinks that "this is my character from birth" Actually it is a form of selfish character that does not want to change its bad character to be better.Profetik literally comes from English, that is prophet or prophetic, which means prophet, prophethood, or apostolic. The son gives the meaning that the prophet is possessing a trait or characteristic of a prophet, or is predictive, predictable. Like a prophet, propheticism means carrying out the divine mission manifested in all noble humanity activities